SOCIAL ACTIVITY OF CHILDREN WITH DISABILITIES THROUGH ARTISTIC CREATION (Archive of Conferences, 2021)
The article analyzes the effective use of art and artistic creativity in increasing the social activity of children with disabilities, as well as the pedagogical and psychological factors required of the teacher in this process.